Surgical Issues for Operable Early-Stage Non–Small-Cell Lung Cancer. Issue 6 (20th February 2022) - Donington, Jessica; Schumacher, Lana; Yanagawa, Jane
Abstract : Surgical care for early stage non–small-cell lung cancer continuously evolves with new procedures, techniques and care pathways. The most obvious recent change was the transition to minimally invasive procedures, but numerous other aspects of care have also been refined to improve safety and tolerability. These care advancements are essential as we move into an era with increased early detection as a result of screening and greater indications for the use of adjuvant and neoadjuvant strategies.